Motion detection of objects using ultra-wide band pulses - Teng, Kian Leong. (2012)
This report contains information pertaining to the knowledge and understanding the author had gained during the entire final year project (FYP) period. The report also discusses about the theory behind ultra-wide band (UWB) and how UWB pulses can be used to detect the motion of an object and the relative position of the object from the antenna group.